This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
2 n is always even for all positive integers.
Therefore, 2 n − 1 is always odd, irrespective of n.
Now if n is even, there is no solution.
Therefore n is odd.
But 2 n − 1 ≡ 0 ( m o d n ) ---required to prove
⇒ 2 n ≡ 1 ( m o d n ) ---(1)
But 2 n − 1 ≡ 1 ( m o d n ) ---- By Fermat's Little Theorem as n is odd ---(2)
Condition (1) and Condition (2) simultaneously cannot be satisfied.
Therefore, n = 1 (as all integers are divisible by 1)